Unfunded pension systems : ageing and migration - Uebelmesser, Silke (Contributions to economic analysis, 2004)
Pension systems in most industrialised countries are unfunded, i.e. they are pay-as-you-go financed and thus depend on a well-balanced ratio (old) recipients to (young) contributors. This so-called dependency ratio will worsen significantly in the next few decades due to two developments: ageing of the population and increased labour mobility. This book analyses the viability of unfunded pension systems in the presence of the projected demographic evolution. The analysis focuses on questions concerning a) efficiency considerations and the possibility of welfare improvements; b) political econom.